Nomeação e fluência verbal em portadores de esclerose múltipla - Guaresi, Ronei (2012)
This investigative work, intitled Naming and verbal fluency in patients with multiple sclerosis , is developed through two studies: the first crosssectional and correlational (Study A) and the second case study (study B). The objectives of the study are: to investigate language functioning through naming ability and verbal fluency in patients with multiple sclerosis; to check the connections between performances on naming and verbal fluency and performance on other neuropsychological tests; to verify the influence of gender and education variables on performance on language and cognitive tests; to evaluate the language skills of patients diagnosed with multiple sclerosis with focus on dysarthria and dysgraphia; to evaluate intensity of neuronal activation the pattern in patients in verbal fluency tasks - phonological and semantic and naming, through functional magnetic resonance technique. Neuropsychological assessments were performed in 42 patients with multiple sclerosis and in 30 participants of a control group. The evaluations were compared to the base of patients with multiple sclerosis of Hospital São Lucas of the PUCRS. In addition we evaluated a patient with Relapsing-Remitting Multiple Sclerosis through reading assignments, copying and spontaneous speech, and also through functional magnetic resonance imaging in naming task, phonological and semantical verbal fluency. The results allowed us to make the following statements: verbal fluency, both semantic and phonological, is impaired in patients with multiple sclerosis; naming is not affected in these patients. Although multiple sclerosis compromises verbal fluency, it does not necessarily compromise memory and intelligence; there is a close relationship between fluency deficits and reduced speed of information processing; gender and education variables do not affect cognitive performance in these patients, except in the Vocabulary subtest. The results of the case study allow us to say: the subject had a significant level of dysgraphia but did not show dysarthria, which reinforces the heterogeneous symptomatic manifestations of the disease; Neuroimaging analysis showed crucial injuries of the disease; the activations in the task of naming and fluency occur predominantly in the left hemisphere with less intense parallel activations in the right hemisphere, which may suggest recruitment of nerve cells due to injuries in the temporal lobe of the left hemisphere.